Marine environmental regulation and green technology innovation: evidence from enterprises in coastal areas of China - Jiang, Junchen; Sun, Han (Frontiers in Marine Science, 2025)
It is of great significance to explore the effect of marine environmental policies to promote the sustainable development of the marine economy. This article takes the ‘National Marine Ecological Civilization Demoznstration Zone’ (hereinafter referred to as the ‘Demonstration Zone’) as a quasi-natural experiment and adopts the difference-in-difference method to explore the effects of marine environmental regulation on green technology innovation of micro-enterprises in coastal areas and on the high-quality development of the regional economy. This article finds that marine environmental regulation can promote the green technology innovation of enterprises in coastal areas. The mechanism analyses show that marine environmental regulation increases the government’s attention to the environment and promotes industrial structure upgrading, thus positively affecting local enterprises’ green technology innovation. Cross-sectional analyses show that the increase in green technology innovation is more pronounced in resource-based cities, areas with high marine economic dependence and high green finance development, as well as in enterprises with low financial constraints and marine-related enterprises. Additionally, marine environmental regulation significantly increases green invention patents and independent green innovation by enterprises in coastal areas. At the macro level, we find that the impact of marine environmental regulation on green technology innovation ultimately leads to high-quality development of the local economy. Based on the above results, this article suggests that the government should actively explore and practice the construction of marine environmental ecological civilization, and further improve marine environmental regulation to encourage firms to carry out green technological innovation activities.